Resilience in crisis: economic coping strategies of informal sector households during the COVID-19 pandemic in Jambi City, Indonesia - Junaidi Junaidi; Nyimas Dian Maisyarah; Al Parok Al Parok; Hardiani Hardiani (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2023)
This study aims to analyze: 1) the socio-economic characteristics of households of informal sector workers in Jambi City; 2) the coping strategies of these households in facing the impacts of the COVID-19 pandemic; 3) the influence of household socio-economic characteristics on the economic coping strategies of informal sector workers in Jambi City. The primary data used in this study were sourced from a survey of households of informal sector workers in Jambi City. The analysis utilized descriptive statistical tools and structural equation modeling (SEM). The findings of the study reveal that: 1) informal sector workers are generally of productive age, with relatively good education, and predominantly engaged in trading and daily wage labor; 2) the COVID-19 pandemic has negatively impacted the social conditions of these households, particularly in terms of income, savings, and non-food expenditures; 3) in the context of economic coping strategies, the strategy of generating additional income is more commonly employed by these households compared to cutting back expenses; 4) the characteristics of the wife and the family significantly influence the coping strategies adopted by households of informal sector workers. In contrast, the characteristics of the household head do not have a significant impact.